Function, sexual dimorphism and intraspecific variation of the bizarre rostral structures of the extinct beaked whale, Globicetus hiberus - Duarte, João Muchagata Madeira (2016)
Ziphiids (commonly known as beaked whales) are deep-diving, echolocation-user odontocetes. The recently named Pliocene Globicetus hiberus bears a peculiar large bony sphere in the rostrum, the mesorostral process of the premaxillae or MPP. The origin and function of MPP is mysterious, but hypotheses are addressed: 1. malformation, deformity or disease; 2. ballast; 3. intraspecific fighting; 4. reflection and directional aim of the sound beam; 5. increasing the velocity of sound waves; 6. sound barrier; and 7. secondary sexual organ. Some hypotheses are rejected (1, 2, 6), others may play a secondary role (3, 4, 5) and we suggest the secondary sexual organ (7) as the most likely explanation. The MPP varies in size in the six specimens studied. During life, MPP grows allometrically in a subgroup but not in the other, suggesting that one subgroup corresponds to males and the other to females (sexual dimorphism). Beaked whales are able to perceive bones as distinctive echoic images with their sonar; therefore the MPP may work as a secondary sexual organ, the so-called “antlers inside” hypothesis; Função, dimorfismo sexual e variação intraespecífica das estruturas rostrais bizarras na baleia-de-bico extinta Globicetus hiberus Resumo: Zifídeos (vulgarmente conhecidos como baleias de bico) são odontocetes ecolocalizadores capazes de efetuar mergulhos de grande profundidade. O recentemente nomeado Globicetus hiberus do Plioceno, exibe uma peculiar e grande esfera óssea no rostro, o processo mesorostral da pré-maxila ou MPP. A origem e função do MPP é misterioso, mas algumas hipóteses são abordadas: 1. malformação, doença ou deformidade; 2. lastro; 3. luta intraespecífica; 4. reflexão e orientação do feixe de som; 5. aumento da velocidade das ondas sonoras; 6. barreira sonora; e 7. órgão sexual secundário. Algumas hipóteses são rejeitadas (1, 2, 6), outros podem desempenhar um papel secundário (3, 4, 5) e sugerimos o órgão sexual secundário (7) como a melhor hipótese. O MPP varia de tamanho nos seis espécimes estudados. Durante a vida, o MPP cresce alométricamente apenas em um subgrupo, sugerindo que um deles corresponde a machos e o outro a fêmeas (dimorfismo sexual). Estas baleias seriam capazes de detetar ossos como imagens ecóicas distintas com o seu sonar, portanto, o MPP poderia funcionar como um órgão sexual secundário, a chamado hipótese das “hastes internas”.